Теоретико-методологічні проблеми дослідження основних сфер конституційного регулювання - Бабенко, К.А. (Часопис Київського університету права, 2009)
Автор статьи обращается к исследованию основных теоретико-методологических подходов анализа и систематизации сфер конституционного регулирования, которые обоснованы в современной науке конституционного права. Особое внимание уделено проблеме изменения основных целей и приоритетов конституционного регулирования в контексты становления Украины как демократического и правового государства. The author of investigates the basic theoretical and methodological approaches in the analysis and classifying of spheres of the constitutional regulation, which are used in a contemporary science of the constitutional law. The special attention is given to a problem of transformation of the basic purposes and priorities of the constitutional regulation in the contexts of Ukraine's development as a democratic state and the state of law.